(HDEP): Coronavirus (SARS-CoV-2) COVID-19 Pandemic System Model Example Hospital Disaster and Emergency Plan in Biological Disasters. Issue 1 (2022) - Artik, Yakup; Varol, Nehir; Cesur, Nevra Pelin
No abstract available